[OP.2B.09] PATIENTS WITH ADVANCED KIDNEY DISEASE AND NEPHROANGIOSCLEROSIS MIGHT NOT BENEFIT OF STRICT BLOOD PRESSURE CONTROL. (September 2016) - Vettoretti, S.; Caldiroli, L.; Azzini, V.; Meazza, R.; Villarini, A.; Marcucci, M.; Alfieri, C.; Messa, P.
Abstract : Objective: Blood pressure (BP) targets in chronic kidney disease (CKD) may differ in accordance with the etiology of CKD. We investigated if BP targets recommended by 2013 ESH guidelines for CKD patients are equally effective in subjects with nephroangiosclerosis (NAS+) respect to those with other nephropathies (NAS-). Design and method: We analyzed 148 hypertensive patients with CKD (stages 3b-4), NAS+ (n = 66) and NAS- (n = 82). We collected at two visits: anamnesis, BP, blood and 24 h urinary samples. BP was measured as the average of three office determinations per visit as well as 24 h ambulatory monitoring (ABPM). eGFR was determined by CKD-EPI formula and eGFR decline as: (eGFR2-eGFR1)/months of follow up. Results: NAS+ and NAS- did not differ regarding: age (74 ± 9 vs 71 ± 9 years; p = 0, 09), prevalence of diabetes (38 vs 50%; p = 0, 16), Charlson index (5, 9 ± 2, 2 vs 6, 1 ± 2, 3; p = 0, 6), follow up (20 ± 9 vs 19 ± 9 months; p = 0, 3); number of anti-hypertensive drugs (2, 7 ± 1 vs 2, 8 ± 1, 4; P = 0, 5), use of RAS inhibitors (60vs56%; p = 0, 6) and diuretics (55vs56%; p = 0, 9). NAS+ and NAS- had comparable eGFR at visit 1 (35 ± 9 vs 35 ± 7 ml/min; p = 0.9) and at visit 2 (32 ± 12 vs 33 ± 9 ml/min; p = 0, 8). NAS+ had higher 24 h proteinuria at both visits: 312 ± 355 vs 780 ± 994 mg, p = 0, 0004 and 357 ± 381 vs 848 ± 924 mg, p < 0, 0001. In NAS+ and NAS- office BP was: SBP1 140 ± 20 vs 142 ± 20 mmHg, p = 0, 4; DBP1 81 ± 11 vs 81 ± 9 mmHg¸ p = 0, 9; SBP2 138 ± 17 vs 138 ± 16, p = 0, 8; DBP2 78 ± 12 vs 80 ± 13, p = 0, 7; ABPM was: PAS24h1 132 ± 15 vs 132 ± 12 mmHg, p = 0, 7; PAD24h1 71 ± 8 vs 72 ± 8 mmHg, p = 0, 7; PAS24h2 131 ± 11 vs 132 ± 11 mmHg, p = 0, 9; PAD24h2 71 ± 8 vs 72 ± 9, p = 0, 6. Patients with office BP at target at both visits were: 27vs18%; p = 0, 2 in NAS+ and NAS-. Patients with office BP at target at both visits demonstrated an increase of eGFR in NAS- (0, 37 ± 1, 15 vs −0, 04 ± 0, 51 ml/min/month; p = 0, 03) and a not significant decrease of eGFR in NAS+ (−0.02 ± 0, 63 vs −0, 14 ± 0, 28 ml/min/month; p = 0, 4); independently of: BP and proteinuria variations, age, diabetes, Charlson index and duration of follow up. Conclusions: In patients with CKD and NAS+, differently from NAS-, BP targets recommended by ESH guidelines are not renoprotective.